2020
DOI: 10.18632/oncotarget.27531
|View full text |Cite
|
Sign up to set email alerts
|

Exosome mediated miR-155 delivery confers cisplatin chemoresistance in oral cancer cells via epithelial-mesenchymal transition

Abstract: Cisplatin is used as chemotherapeutic drug for oral squamous cell carcinoma (OSCC). However, OSCC cells develop resistance following long-term cisplatin exposure. Resistance against cisplatin chemo-therapy is accredited to the process of epithelial-to-mesenchymal transition, which in-turn has been linked to tumorrecurrence. miRNA deregulation, a common event in cancer, plays contributory role in chemo-resistance. Exosomes acts as the natural cargo for miRNA and facilitates inter-cell communication in the tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 60 publications
4
55
0
Order By: Relevance
“…Exosomes isolated from CIS-resistant cell lines contained a higher concentration of miR-21 in accordance with the parental cells' increased cisplatin resistance, which indicates that miR-21 may be a potential target against chemoresistance (Liu et al, 2017). The underlying mechanism is considered related to EMT and decreased DNA damage in cancer cells (Cui et al, 2020;Kirave et al, 2020). Some miRNAs were downregulated during chemoresistance.…”
Section: Mirnamentioning
confidence: 89%
“…Exosomes isolated from CIS-resistant cell lines contained a higher concentration of miR-21 in accordance with the parental cells' increased cisplatin resistance, which indicates that miR-21 may be a potential target against chemoresistance (Liu et al, 2017). The underlying mechanism is considered related to EMT and decreased DNA damage in cancer cells (Cui et al, 2020;Kirave et al, 2020). Some miRNAs were downregulated during chemoresistance.…”
Section: Mirnamentioning
confidence: 89%
“…Exosomes isolated from CIS-resistant cell lines contained a higher concentration of miR-21 in accordance with the parental cells' increased cisplatin resistance, which indicates that miR-21 may be a potential target against chemoresistance (Liu et al 2017). The underlying mechanism is considered related to EMT and decreased DNA damage in cancer cells (Cui et al 2020b;Kirave et al 2020). Some miRNAs were downregulated during chemoresistance.…”
Section: Exosomal Mirnas In Chemoresistancementioning
confidence: 89%
“…However, Chemoresistance is a significant challenge for OSCC treatment with no clear mechanism. Several studies have shown that miRNAs in exosomes of both healthy and tumor cells can manipulate this phenomenon (Cui et al 2020b;Kirave et al 2020;Qin et al 2019). Some miRNAs are upregulated during chemotherapy, which can enhance chemoresistance against antitumor drugs such as cisplatin (CIS) and docetaxel (DTX).…”
Section: Exosomal Mirnas In Chemoresistancementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, miR-155 inhibited proliferation, migration, invasion and triggered cell cycle arrest and apoptosis via regulating the expression of collagen triple repeat containing 1 (CTHRC1) in human melanoma 27 . Moreover, exosome-mediated miR-155 delivery led to cisplatin resistance of oral squamous cell carcinoma (OSCC) cells via induction of EMT 28 . However, it is unclear whether miR-155 targets FBXO22 in human cancer cells, which is required to further determine.…”
Section: Upstream Regulators Of Fbxo22mentioning
confidence: 99%